Problems of Domestic and Public Work: A Case Study of Career Women in Bandung - Pauzian, Muhamad Hilmi; Huriani, Yeni; Zulaiha, Eni (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2023)
This paper will discuss the problems of women with a double burden, both domestic and public. The case studies were women working in Cinunuk Village, Cileunyi District, Bandung Regency, West Java. This paper uses qualitative methods by collecting data through in-depth interviews. The results and discussion of this study include the role of women in the domestic sphere, the role of women in reviving the family economy, and the problems of women working domestically and in public. This study concludes that career women have a double burden, both domestic and public. On the one hand, they have to carry out their obligations as a housewife, such as preparing the needs of their husband and children, preparing meals, cleaning the house, educating children, etc. They also have to work outside the home helping the family economy. However, by having this dual role, career women in Cinunuk Village, Cilenyi District, Bandung Regency have problems or consequences that they get from these dual roles. First, they must be able to share their time and feel tired. Second, lack of attention to children. Third, household. Fourth, talk about less wearing. However, this problem will not become serious when there is a gender partnership in the family. This partnership is carried out through the division of domestic and public work. This partnership in the family can share tasks and roles in the family, transparency in the family, accountability in the family, good governance in the family.